Influence of Age, Estrogen receptor (ER),Progesterone receptor (PR) and Epidermal growth factor -2 (HER-2) in Breast Carcinoma Patient in correlation with Radionuclide Bone Scan – Single Institute Based Experience (Bangladesh Journal of Nuclear Medicine, 2021)
Background: Breast carcinoma is a common type of malignancy in women worldwide. Radionuclide bone scintigraphy is recognized choice of investigation for the detection of bone metastases both in asymptomatic and symptomatic patients. Biomarkers like Estrogen Receptor (ER), Progesterone Receptor (PR), Human Epidermal growth factor -2 (HER-2) also play important role in the management and prognosis of breast cancer. The study was aimed to find out the relationship between the MDP bone scan findingsand hormone receptor and HER-2 status of breast carcinoma patients referred to the Institute of Nuclear Medicine and Allied Sciences (INMAS), Mitford, Dhaka.Patients and Methods: This cross sectional study was conducted among 301 breast carcinoma patients between January 2018 and December 2019. Planar bone scan and SPECT (if needed) was done to all the patients after intravenous injection of 99mTc-MDP. Receptor status (ER, PR and HER-2) were documented from the patient’s medical records. Breast tumors were classified as (a) Triple positive- HER2-, ER-, and PR-positive) (b) Triple negative- HER2-, ER-, and PR-negative (c) Hormonereceptor (HR) positive (ER+/PR+) with HER-2 negative and d) HR negative (ER-/PR-) with HER-2 positive.Patients were broadly grouped according to age as A. less than 50 years (n = 59) and B. more than 50 (n = 260 ) years.Results: The mean age of the patients enrolled for this study was 59.02±9.3 with range of 32 to 81 years. Out of the 301 patients, positive bone scans were found in 105 (34.8%) and negative bone scan were found 196 (66.2%). Patients of group A ( 50years) patients having HR+/HER2- receptor status showed 16% solitary metastases, 53.2% multiple metastases, 33.3% extensive bony metastases, 13.6% bone with visceral metastases. Triple negative subtype showed 36.0 % solitary metastases, 19.1% bone with visceral metastases. Triple positive subtype group had 40.0% solitary metastases, 34.0 % multiple metastases, 66.7% extensive bony metastases, and 13.6% bone with visceral metastases. HR-/HER-2+ subtype group had 8% solitary metastases, 12.8% multiple metastases, and 18.2 % bone metastases with visceral involvement Overall relationship between bone scan and hormone receptor subtype, showed that most of the patients had HR+/ HER-2-(35.2%) subtype and 25.6% patient had triple positive, 23.3% patient had triple negative and 15.9% patient had HR-/HER-2 – receptor subtype. This study showed the visceral involvement with bone metastases (13 % in HR+/HER-2- 52.2 % in triple negative, 13 % in triple positive, 21.7 % in HR-/HER-2+subtype). Highest bone only metastases (35) in triple positive and HR+/HER-2-(31) subtype. Most of the patiens who had bone metastases with visceral involvement belong to triple negative (52.2%) and HER-2 subtypes -HR-/HER-2+ (21.7%). The result was significant (P